Peran Guru Bimbingan Dan Konseling Pada Masa Pandemi Covid-19: Studi Fenomenologi Madrasah Aliyah Di Jawa Timur - Hidayat, A. Taufiq; Habsy, Bakhrudin All (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
The transition of learning during the COVID-19 pandemic from offline to online and then offline again certainly has its own impact on students. Guidance and Counseling (BK) teachers are expected to have a clear role. This study aims to determine the role of guidance and counseling teachers during the COVID-19 pandemic. To obtain data, the researcher conducted interviews with the selected research subjects because they had the capacity according to the research theme (purpose sampling). Based on the results of the interviews conducted, the researchers found: (1) The role of the BK teacher Ing ngarso sung tuladha, was carried out by providing good examples for students who came from their own initiative, the role was in accordance with the covert role or personal role where the behavior was made purely from sincerity and has a positive impact on the environment, (2) the role of the BK teacher Ing madya mangun karsa where when in his own environment he gives encouragement either directly or indirectly, this is in accordance with the role of overt or the role of the public that makes the surrounding environment feel excited, ( 3) The role of the BK teacher, tut wuri handayani, where the BK teacher shows his performance professionally so that colleagues are also encouraged to improve their performance, this role is in accordance with the descriptive role theory of descriptive roles or concepts that make the surrounding environment have a concept of what the subject is doing repeatedly.